THE RELATIONSHIP BETWEEN STUDENTS’ ATTITUDE AND LEARNING MOTIVATION TOWARD THE STUDENTS’ ENGLISH ACHIEVEMENT AT THE FIRST GRADE IN SMAN 3 TOLITOLI - Fajar Yuniawati (Jurnal Madako Education, 2020)
The  aims  of  this  research  is  to  find  out  the  significant  correlation  between  the students’ attitude toward the students English achievement, to find out the significant correlation between learning motivation toward the students English achievement, and to find out the significant simultaneously between students’ attitude and learning motivation toward the students English achievement at the first grade in SMAN 3 Tolitoli. This research use quantitative analysis, the population of this research is the first grade of SMAN 3 Tolitoli and the sample of this research are 33 students. The researcher used questionnaire   as the main technique of collecting the data, the result of this research showed that there was significant correlation between students’ attitude toward the students English achievement, it is proved Tcount2,1113>Ttable 2,045. The second, there was no significant correlation between learning motivation toward the students English achievement, it is proved Tcont0,3234<T table 2,045,  the  third  there  was  no  significant  simultaneously  between  students’  attitude  and learning  motivation  toward  the  students  English  achievement  it  is  proved  sig  f  change 0,136>0,05.  The  conclusion  from  this  research  there  was  no  significant  simultaneously between students’ attitude and learning motivation toward the students English achievement.Keyword: Attitude, motivation, achievement